Pengaruh Budaya Organisasi dan Employee Engagement terhadap Kinerja Karyawan pada PT PLN (Persero) Area Bekasi - Joushan, Shindie Aulia; Syamsun, Muhammad; Kartika, Lindawati (Jurnal Aplikasi Manajemen, 2015)
Electricity is a necessity that can not be separated from human's life. PLN as theelectric service providers in Indonesia are required to improve its performance. The aims ofthis study are (1) analyzing the influence of organizational culture to employee engagement,(2) analyzing the influence of organizational culture and employee engagement to employeeperformance at PT PLN (Persero) Bekasi area. Data processed and analyzed by DescriptiveAnalysis, Structural Equation Modeling Analysis supported by microsoft excel, SPSS 16.0for windows, and SmartPLS 3.0. The results of this study are: (1) Organizational culture hasa significant effect on employee engagement; (2) Organizational culture has a significanteffect on employee performance. However, employee engagement has no significant effect onthe employee performance.